Method for manufacturing conductive wiring substrates, laminates, and multilayer laminates

JP2026169186APending Publication Date: 2026-10-16TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2026060836
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-12-09
Filing Date
2026-04-02
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、煩雑なプロセス管理を要することなく、表面に段差を有する基材を用いた場合であっても、段差部の導電配線の断線を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169186000001_ABST
    Figure 2026169186000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a conductive wiring substrate that can suppress disconnection of conductive wiring at stepped portions, even when using a substrate with stepped surfaces, without requiring complicated process control. [Solution] A method for manufacturing a conductive wiring substrate having conductive wiring on a substrate, comprising: a transfer step of transferring the wiring pattern to the substrate via an adhesive layer, in which a release substrate with a wiring pattern having a wiring pattern on a release substrate and a substrate are arranged with an adhesive layer between them so that the wiring pattern faces the substrate side; a peeling step of peeling off the release substrate; and a firing step of firing the wiring pattern and adhesive layer to form conductive wiring on the substrate, wherein the wiring pattern contains inorganic particles and organic components, and the inorganic particle content in the wiring pattern is 60 to 90% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for manufacturing a conductive wiring substrate, a laminate, and a multilayer laminate. [Background technology]

[0002] Examples of methods for forming conductive wiring on substrates such as glass substrates and ceramic substrates include a method of screen-printing a fired conductive paste on a substrate and firing it, a method of screen-printing a photosensitive conductive paste on a substrate, forming a pattern by photolithography and curing it, and a method of forming a conductive film on a substrate by a method such as vapor deposition and then etching it. However, these methods have had problems in terms of higher definition of conductive wiring and productivity accompanying the recent miniaturization and higher performance of electronic components. Accordingly, methods for transferring conductive wiring and the photosensitive layer that is its material onto a substrate have been studied. For example, a heat-resistant wiring board having a metal conductive pattern on its surface, wherein the metal conductive pattern is an electrodeposited metal pattern, and the electrodeposited metal pattern formed on a transfer substrate is transferred to a target substrate via a pressure-sensitive adhesive or an adhesive (see, for example, Patent Document 1), and a method for producing a ceramic green sheet with a conductive pattern, which includes the steps of laminating a substrate with a photosensitive layer on a ceramic green sheet, exposing, and developing (for example, Patent Document 2), have been proposed. Further, as a transfer film for forming conductive patterns such as wiring circuits and electrodes on a base body such as glass, in a transfer film for firing used to form a fired body of a functional pattern by transferring a laminate including the functional pattern onto the surface of the base body and firing the laminate, the transfer film for firing includes a release film and the laminate formed so as to be in contact with one surface of the release film, the laminate further includes a pressure-sensitive adhesive layer for adhering the transfer film for firing to the surface of the base body, and a functional pattern formed between the release film and the pressure-sensitive adhesive layer, the functional pattern contains inorganic powder and a first organic substance that can be removed by firing, the pressure-sensitive adhesive layer contains a second organic substance that can be removed by firing and is different from the first organic substance, and the thermal decomposition temperature (Tdb) of the first organic substance, the thermal decomposition temperature (Tda) of the second organic substance, and the fusing temperature (Tw) of the inorganic powder under the firing conditions when the laminate is transferred to the surface of the base body and fired satisfy the relationship of Tdb<Tda<Tw, and such a transfer film for firing has been proposed (see, for example, Patent Document 3). [Prior Art Documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 11-251722 [Patent Document 2] International Publication No. 2024 / 004461 [Patent Document 3] Japanese Patent Publication No. 2008-307729 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] For example, heater electrodes on car windshields are generally formed near the edge of the windshield to ensure a wide field of view. Furthermore, decorative finishes are often applied to these edges to protect the adhesive bonding the glass to the car body from ultraviolet rays and to reduce sunlight exposure to the driver. Therefore, conductive wiring may be formed across the decorated and undecorated areas of the substrate. However, when such conductive wiring is formed using the techniques described in Patent Documents 1 and 2, the conductive wiring cannot follow the step difference at the boundary between the decorated and undecorated areas, leading to a problem of frequent disconnections at the boundary. Additionally, the technique described in Patent Document 3 requires the lamination of multiple layers, such as intermediate and protective layers, to improve barrier properties and flexibility, resulting in a complex process of controlling the firing process depending on the thermal decomposition temperature of the organic matter contained in each layer.

[0005] Therefore, the present invention aims to provide a method for manufacturing a conductive wiring substrate that can suppress disconnection of conductive wiring at stepped portions, even when a substrate having stepped surfaces is used, without requiring complicated process control. [Means for solving the problem]

[0006] To solve the above problems, the present invention mainly has the following configuration. (1) A method for manufacturing a conductive wiring substrate having conductive wiring on a substrate, A transfer process involves arranging a release substrate with a wiring pattern having a wiring pattern on the release substrate and a base material with an adhesive layer in between so that the wiring pattern faces the base material, and transferring the wiring pattern to the base material via the adhesive layer. A peeling process to remove the release substrate, and a firing process in which the wiring pattern and adhesive layer are fired to form conductive wiring on the substrate, The wiring pattern has these elements in this order, and contains inorganic particles and organic components. A method for manufacturing a conductive wiring substrate, wherein the content of inorganic particles in the wiring pattern is 60 to 90% by mass. (2) In the transfer step, A laminate of a release substrate with an adhesive layer / wire pattern, having a wiring pattern and an adhesive layer on a release substrate, and a substrate are placed so that the adhesive layer faces the substrate, and the adhesive layer and wiring pattern are transferred to the substrate. (1) A method for manufacturing a conductive wiring board as described in (1). (3) In the transfer step, A release substrate with a wiring pattern, having a wiring pattern on the release substrate, and an adhesive layer / substrate laminate, having an adhesive layer on the substrate, are arranged so that the wiring pattern faces the adhesive layer side of the adhesive layer / substrate laminate, and the wiring pattern is transferred to the adhesive layer / substrate laminate. (1) A method for manufacturing a conductive wiring board as described in (1). (4) In the transfer step, A laminate of a release substrate with an adhesive layer pattern / wired layer pattern, having a laminate of a wiring pattern and an adhesive layer pattern on a release substrate, and a substrate are placed so that the adhesive layer pattern faces the substrate, and the adhesive layer pattern and wiring pattern are transferred to the substrate. (1) A method for manufacturing a conductive wiring board as described in (1). (5) A method for manufacturing a conductive wiring substrate according to any one of (1) to (4), wherein the conductive wiring contains silver, copper, palladium, molybdenum, tungsten and / or nickel. (6) A method for manufacturing a conductive wiring substrate according to any one of (1) to (5), wherein the substrate has steps on its surface. (7) A method for manufacturing a conductive wiring substrate according to any one of (1) to (6), comprising the step of forming a wiring pattern on the release substrate by photolithography using a photosensitive paste containing inorganic particles and organic components, wherein the organic components contain photosensitive components. (8) A method for manufacturing a conductive wiring substrate according to any one of (1) to (7), wherein the inorganic particles contain 10 to 25 volume percent of glass frit in the total inorganic particles. (9) The method for manufacturing a conductive wiring substrate according to (8), wherein the glass frit contains bismuth oxide. (10) The method for manufacturing a conductive wiring substrate according to (8) or (9), wherein the glass frit has a softening point in the range of 420 to 800°C, the softening point is higher than the decomposition temperature of the organic component with the highest decomposition temperature among the organic components in the wiring pattern and the adhesive layer, and in the firing step, the glass frit is fired at a temperature higher than the softening point. (11) A method for manufacturing a conductive wiring substrate according to any one of (1) to (10), wherein the inorganic particles contain silicon dioxide particles in an amount of 5 volume% or more of the total inorganic particles. (12) A method for manufacturing a conductive wiring substrate according to any one of (1) to (11), wherein the thickness of the adhesive layer is 1 to 50 μm. (13) A method for manufacturing a conductive wiring board according to any one of (8) to (12), wherein in the firing step, the glass frit is heat-treated at a temperature lower than its softening point for 5 minutes or more, and then fired at a temperature higher than its softening point. (14) The method for manufacturing a conductive wiring substrate according to (13), wherein the thickness of the adhesive layer is 10 to 50 μm. (15) The height of the step is T0 μm, and the film thickness of the wiring pattern is T a μm, the thickness of the adhesive layer is T b When the unit is μm, T0, T a and T b A method for manufacturing a conductive wiring board as described in any of (6) to (14), wherein the following formula (1) is satisfied. T a ×T b ≥T0(1) (16) A method for manufacturing a conductive wiring substrate according to any one of (1) to (15), wherein conductive wiring is provided on both sides and sides of the substrate. (17) A method for producing a laminate having conductive wiring and a green sheet on a green sheet, the method comprising: a transfer step of arranging a release base material with a wiring pattern having a wiring pattern on a release base material and a first green sheet such that the wiring pattern faces the first green sheet side via an adhesive layer, and transferring the wiring pattern to the first green sheet via the adhesive layer, a peeling step of peeling off the release base material, a laminating step of laminating a second green sheet on the wiring pattern side, and a firing step of firing the wiring pattern and the adhesive layer to form conductive wiring between the green sheets, which are performed in this order, wherein the wiring pattern contains inorganic particles and an organic component, and the content of the inorganic particles in the wiring pattern is 60 to 90 mass%, the method for producing a laminate. (18) A method for producing a multilayer laminate formed by laminating a plurality of green sheets with conductive wiring and green sheets, the method comprising: producing a plurality of green sheets with a wiring pattern having an adhesive layer by a method including, in this order, a transfer step of arranging a release base material with a wiring pattern having a wiring pattern on a release base material and a first green sheet such that the wiring pattern faces the first green sheet side via an adhesive layer, and transferring the wiring pattern to the first green sheet via the adhesive layer, and a peeling step of peeling off the release base material, laminating the obtained plurality of green sheets with a wiring pattern having an adhesive layer, further arranging a second green sheet on the wiring pattern side of the outermost portion, and collectively laminating them, and a firing step of firing the wiring pattern and the adhesive layer to form conductive wiring between the green sheets, which are performed in this order, wherein the wiring pattern contains inorganic particles and an organic component, and the content of the inorganic particles in the wiring pattern is 60 to 90 mass%, the method for producing a multilayer laminate. Effects of the Invention

[0007] According to the present invention, even when a substrate having steps on its surface is used, disconnection of conductive wiring at the stepped portion can be suppressed without requiring complicated process control. [Brief explanation of the drawing]

[0008] [Figure 1] This is a schematic diagram showing an example of a method for manufacturing a conductive wiring substrate according to the present invention. [Figure 2] This is a schematic diagram showing another example of the method for manufacturing a conductive wiring substrate according to the present invention. [Figure 3] This is a schematic diagram showing another example of the method for manufacturing a conductive wiring substrate according to the present invention. [Modes for carrying out the invention]

[0009] The present invention provides a method for manufacturing a conductive wiring substrate having conductive wiring on a substrate, comprising: a transfer step of transferring the wiring pattern to the substrate via an adhesive layer, arranging a release substrate with a wiring pattern having a wiring pattern on a release substrate and a substrate with an adhesive layer so that the wiring pattern faces the substrate side; a peeling step of peeling off the release substrate; and a firing step of firing the wiring pattern and adhesive layer to form conductive wiring on the substrate. Here, the wiring pattern becomes conductive wiring by exhibiting conductivity in the firing step, and is formed corresponding to the shape of the conductive wiring. In the transfer step, since the wiring pattern is transferred to the substrate via an adhesive layer, the wiring pattern can be transferred to a desired substrate at low temperature and low pressure. In the firing step, by firing both the wiring pattern and the adhesive layer, the wiring pattern becomes conductive wiring, the adhesive layer component is removed by deash, and conductive wiring is directly formed on the substrate. The adhesive layer may be patterned to correspond to the wiring pattern. In the present invention, "forming conductive wiring on the substrate" means forming conductive wiring directly on the substrate, that is, the conductive wiring is in direct contact with the substrate without an adhesive layer. In the technology described in Patent Document 1, an electrodeposited metal pattern is adhered to the substrate by a heat-fused inorganic component. In contrast, in the present invention, conductive wiring is formed directly on the substrate by deash removal of the adhesive layer component. This allows conductive wiring to follow the steps even when a substrate with steps on its surface is used, thereby suppressing disconnection of the conductive wiring at the steps. Furthermore, in the present invention, it is important that the wiring pattern contains inorganic particles and organic components, with the inorganic particle content in the wiring pattern being 60 to 90% by mass. If the inorganic particle content is less than 60% by mass, the proportion of organic components increases, and the amount of deash components increases during the firing process. As a result, gases generated from the organic components are less likely to be released into the atmosphere, reducing the adhesion between the conductive wiring and the substrate, making disconnection more likely at the steps. On the other hand, if the inorganic particle content exceeds 90% by mass, the flexibility of the wiring pattern is impaired, making disconnection more likely at the steps.In the technology described in Patent Document 3, a protective layer is provided to suppress cracking of the functional pattern when bent, whereas in the present invention, by including a certain amount of organic components in the wiring pattern, the flexibility of the wiring pattern is improved, and disconnection of conductive wiring at stepped portions can be suppressed without requiring an additional layer.

[0010] Methods for transferring a wiring pattern to a substrate via an adhesive layer include, for example, a method of transferring the adhesive layer and wiring pattern to a substrate by arranging an adhesive layer / release substrate laminate having a wiring pattern and an adhesive layer on a release substrate and a substrate so that the adhesive layer faces the substrate side; a method of transferring the wiring pattern to an adhesive layer / substrate laminate by arranging an adhesive layer / substrate laminate having an adhesive layer on a release substrate and an adhesive layer on a substrate so that the wiring pattern faces the adhesive layer side of the adhesive layer / substrate laminate; a method of transferring the adhesive layer and wiring pattern to a substrate by arranging a release substrate with a wiring pattern having a wiring pattern on a release substrate, a substrate and an adhesive layer so that the wiring pattern faces the substrate side via the adhesive layer; and a method of transferring the adhesive layer pattern and wiring pattern to a substrate by arranging an adhesive layer pattern / release substrate laminate having a laminate of a wiring pattern and an adhesive layer pattern on a release substrate and a substrate so that the adhesive layer pattern faces the substrate side. Among these methods, the method using a release substrate laminate with an adhesive layer / wiring pattern is preferred from the viewpoint of protecting the wiring pattern. Furthermore, the method using a release substrate laminate with an adhesive layer / wiring pattern can reduce the amount of adhesive layer component that needs to be deashed and removed.

[0011] Figure 1 shows a schematic diagram of an example of a method for manufacturing a conductive wiring substrate according to the present invention. First, as shown in Figure 1(a), a release substrate with a wiring pattern 2 is prepared, which has a wiring pattern 2 on a release substrate 1. Next, as shown in Figure 1(b), an adhesive layer 3 is formed on the release substrate with the wiring pattern to obtain an adhesive layer / release substrate with wiring pattern laminate. Next, as shown in Figure 1(c), the adhesive layer / release substrate with wiring pattern laminate, which has a wiring pattern 2 and an adhesive layer 3 on a release substrate 1, and a substrate 4 are placed so that the adhesive layer 3 faces the substrate 4, and the adhesive layer 3 and wiring pattern 2 are transferred to the substrate 4 (transfer step). Furthermore, as shown in Figure 1(d), the release substrate 1 is peeled off (peeling step). Finally, the wiring pattern 2 and adhesive layer 3 are fired to form conductive wiring 5 on the substrate 4 (firing step).

[0012] Figure 2 shows a schematic diagram of a method for manufacturing a conductive wiring substrate according to the present invention, specifically when the substrate has a step on its surface. Similar to Figure 1, as shown in Figure 2(a), a release substrate with a wiring pattern 2 is prepared on a release substrate 1, and as shown in Figure 2(b), an adhesive layer 3 is formed on the release substrate with the wiring pattern to obtain an adhesive layer / release substrate with wiring pattern laminate. Next, as shown in Figure 2(c), the adhesive layer / release substrate with wiring pattern laminate, which has the wiring pattern 2 and adhesive layer 3 on the release substrate 1, and the substrate 7 having a step are placed so that the adhesive layer 3 faces the surface of the substrate 7 including the step portion 6, and the adhesive layer 3 and wiring pattern 2 are transferred to the substrate 7 having a step (transfer step). Furthermore, as shown in Figure 2(d), the release substrate 1 is peeled off (peeling step). Finally, the wiring pattern 2 and adhesive layer 3 are fired to form conductive wiring 5 on the substrate 7 having a step (firing step).

[0013] Figure 3 shows a schematic diagram of a method for manufacturing a conductive wiring substrate using a patterned adhesive layer, as another example of the method for manufacturing a conductive wiring substrate according to the present invention. First, in order to obtain a release substrate with a wiring pattern to be used in the transfer process, a photosensitive layer 10 and a photosensitive adhesive layer 8 are formed on the release substrate 1 as shown in Figure 3(a). Next, a laminate of an adhesive layer pattern 9 and a wiring pattern 2 is formed on the release substrate by photolithography as shown in Figure 3(b). Next, as shown in Figure 3(c), the adhesive layer pattern / release substrate laminate having the wiring pattern 2 and adhesive layer pattern 9 on the release substrate 1 and a substrate 7 having a step are placed so that the adhesive layer pattern 9 faces the surface of the substrate 7 including the step portion 6, and the adhesive layer pattern 9 and wiring pattern 2 are transferred to the substrate 7 having a step (transfer process). Furthermore, as shown in Figure 3(d), the release substrate 1 is peeled off (peeling process). Finally, the wiring pattern 2 and adhesive layer pattern 9 are fired to form conductive wiring 5 on the substrate 7 which has steps (firing process).

[0014] In the present invention, the release substrate with a wiring pattern used in the transfer process has a wiring pattern formed on it, as shown in Figures 1(a), 2(a), and 3(b). A preferred method for forming the wiring pattern is photolithography using a photosensitive paste. Specifically, it is preferable to have a step of forming a wiring pattern on the release substrate by photolithography using a photosensitive paste containing inorganic particles and organic components, where the organic component contains a photosensitive component. By forming the wiring pattern by photolithography, a higher-resolution pattern can be formed. Furthermore, by photocuring the wiring pattern, the penetration of components from the adhesive layer into the wiring pattern can be suppressed.

[0015] As described above, the release substrate with a wiring pattern used in the transfer process preferably has an adhesive layer on the wiring pattern, and the adhesive layer may have a pattern corresponding to the wiring pattern formed on it, as shown in Figure 3(b). As a method for forming the adhesive layer pattern, photolithography using a photosensitive adhesive paste is preferred, and it is preferable to form the wiring pattern and the adhesive layer pattern together by photolithography on a laminate of a photosensitive layer formed using a photosensitive paste and a photosensitive adhesive layer formed using a photosensitive adhesive paste.

[0016] Examples of substrates for the conductive wiring substrate in the present invention include metal substrates, glass substrates, and green sheets. Examples of substrate shapes include planar shapes and curved shapes.

[0017] According to the present invention, even when a substrate having steps on its surface is used, conductive wiring can be formed following the steps, and disconnection of the conductive wiring in the stepped portion can be suppressed. Therefore, substrates having steps on their surface can be suitably used. Examples of substrates having steps on their surface include glass substrates having a decorated portion and an undecorated portion.

[0018] The step height is preferably 0.1 to 100 μm. By setting the step height to 0.1 μm or more, the effects of the present invention can be more significantly realized. On the other hand, by setting the step height to 100 μm or less, it is easier to follow the step, and the disconnection of conductive wiring at the step can be further suppressed.

[0019] Here, the height of the step can be measured using a stylus-type step meter (for example, "Surfcom®" 1400; manufactured by Tokyo Seimitsu Co., Ltd.). More specifically, the height from the substrate (μm) can be measured at three randomly selected locations on the step using a stylus-type step meter under the conditions of measuring length: 1 mm and scanning speed: 0.3 mm / second, and the average value of these measurements can be calculated. If the average value is less than 1, the second decimal place should be rounded to the first decimal place; if it is 1 or greater, the first decimal place should be rounded to the integer.

[0020] The conductive wiring of the conductive wiring substrate in the present invention preferably contains metals such as silver, gold, copper, platinum, palladium, tin, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, titanium, and indium, or alloys containing these metals, or oxides of these metals. Two or more of these may be contained. Among these, from the viewpoint of low-temperature sinterability and conductivity, it is preferable to contain silver and / or copper, and from the viewpoint of heat resistance and corrosion resistance during high-temperature sintering, it is preferable to contain palladium, molybdenum, tungsten, and / or nickel.

[0021] The conductive wiring is preferably formed by photocuring and firing a photosensitive paste, as described later. The thickness of the conductive wiring is preferably 2 μm or more from the viewpoint of suppressing wire breakage during firing. On the other hand, the thickness of the conductive wiring is preferably 20 μm or less from the viewpoint of promoting the release of gases generated from organic components during firing into the atmosphere. Furthermore, the wire width of the conductive wiring is preferably 5 μm or more from the viewpoint of further suppressing wire breakage during firing.

[0022] The following describes each step in the manufacturing method of the conductive wiring substrate of the present invention.

[0023] (Transfer process) In the transfer process, a release substrate with a wiring pattern having a wiring pattern on a release substrate and a base material are placed with the wiring pattern facing the base material side via an adhesive layer, and the wiring pattern is transferred to the base material via the adhesive layer. Preferred methods include: transferring the adhesive layer and wiring pattern to the base material by placing an adhesive layer / release substrate laminate having a wiring pattern and an adhesive layer on a release substrate and a base material with the adhesive layer facing the base material side; transferring the wiring pattern to the adhesive layer / base material laminate by placing a release substrate with a wiring pattern having a wiring pattern on a release substrate and an adhesive layer / base material laminate having an adhesive layer on a base material with the wiring pattern facing the adhesive layer side of the adhesive layer / base material laminate; and transferring the adhesive layer pattern and wiring pattern to the base material by placing an adhesive layer pattern / release substrate laminate having a laminate of a wiring pattern and an adhesive layer pattern on a release substrate and a base material with the adhesive layer pattern facing the base material side.

[0024] As the release substrate, a film having a release layer is preferred, and the release layer is preferably coated with a release agent. Examples of films include polyester films such as polyethylene terephthalate (PET), polycarbonate films, and polyimide films. Examples of release agents include long-chain alkyl release agents, silicone release agents, and fluorine-based release agents. Two or more of these may be used. Among these, long-chain alkyl release agents are preferred because, even if release agent transfer occurs during the transfer process, they are less likely to cause inhibition of sintering of inorganic particles in subsequent processes, particularly the firing process.

[0025] From a handling standpoint, the thickness of the release substrate is preferably 10 μm or more. On the other hand, from the viewpoint of further improving conformability to the substrate during the transfer process, the thickness of the release substrate is preferably 200 μm or less.

[0026] The wiring pattern contains inorganic particles and organic components, and as mentioned above, the inorganic particle content in the wiring pattern is 60 to 90% by mass. Preferably, the inorganic particle content in the wiring pattern is 70% by mass or more, and preferably 80% by mass or less.

[0027] Here, the inorganic particle content in the wiring pattern can be calculated by peeling or scraping the wiring pattern from the release substrate with the wiring pattern attached, measuring its weight, heating it in a hot air oven at 400°C for 3 hours, measuring its weight again, and calculating the weight change before and after heating. The calculated content should be rounded to the nearest integer. However, if the composition of the wiring pattern is known, it may be calculated from the known composition.

[0028] As mentioned above, the wiring pattern is more preferably formed by photolithography of a photosensitive paste in which the organic components are photosensitive. In this case, the inorganic particles in the photosensitive paste and their content, as described below, are the same in the wiring pattern.

[0029] It is preferable to include conductive particles as inorganic particles that exhibit conductivity by melting and / or fusing during firing. Examples of conductive particles include particles of metals such as silver, gold, copper, platinum, palladium, tin, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, titanium, and indium, as well as alloys containing these metals and oxides of these metals. Two or more of these may be included. Among these, silver and copper particles are preferred from the viewpoint of low-temperature sinterability and conductivity, while palladium, molybdenum, tungsten, and nickel particles are preferred from the viewpoint of heat resistance and corrosion resistance during high-temperature sintering. Conductive particles can be selected according to the firing temperature in the firing process described later. For example, if the firing temperature is less than 1,100°C, silver and copper particles are preferred, and silver particles are more preferred from the viewpoint of stability. On the other hand, if the firing temperature is 1,100°C or higher, palladium, molybdenum, tungsten, and nickel particles are preferred, and molybdenum and tungsten particles are more preferred from the viewpoint of conductivity and thermal stability.

[0030] The content of conductive particles in the photosensitive paste is preferably 65% ​​by volume or more of the total inorganic particles. By increasing the content of conductive particles to 65% by volume or more, the probability of contact between conductive particles during the firing process is improved, the conductivity of the conductive wiring is further improved, and the disconnection of conductive wiring at stepped sections can be further suppressed. The content of conductive particles is more preferably 70% by volume or more.

[0031] It is preferable to further include glass frit as inorganic particles. By including glass frit, the glass frit softens during the firing process, appropriately coating the conductive particles and protecting them from acid, thereby increasing the strength of the conductive wiring and improving its abrasion resistance and acid resistance. In addition, it is possible to improve the adhesion between the conductive wiring and the substrate on the conductive wiring substrate.

[0032] The glass frit preferably contains oxides of Bi, Si, B, Zr, Al, Ca, Ba, Zn, and Mg. It may contain two or more of these. Among these, it is more preferable to contain bismuth oxide, which has low reactivity with acids and a stable crystalline structure, from the viewpoint of further improving the acid resistance of conductive wiring.

[0033] The glass frit preferably has a softening point between 420 and 800°C, and more preferably between 500 and 700°C. Having a softening point above 420°C suppresses the encapsulation of gases generated from organic components into the softened and flowing glass during the firing process described later, promoting gas release into the atmosphere, further suppressing the disconnection of conductive wiring at stepped sections caused by gas encapsulation into the glass, and improving the adhesion between the conductive wiring and the substrate. Having a softening point above 500°C results in a softening point that is sufficiently higher than the decomposition temperature of typical organic components, further improving the adhesion between the conductive wiring and the substrate. On the other hand, having a softening point below 800°C improves the sinterability of the glass frit and further improves the adhesion between the conductive wiring and the substrate. Having a softening point below 700°C provides, in addition to the aforementioned effects, the firing process described later suppresses phase separation between the conductive particles and the glass, thereby increasing the contact area between the conductive particles and the glass. This suppresses the penetration of acidic components and improves acid resistance.

[0034] The softening point of the glass frit is preferably higher than the decomposition temperature of the organic component with the highest decomposition temperature in the photosensitive paste and adhesive layer. By setting the softening point of the glass frit higher than the decomposition temperature of the organic component, when the firing temperature is set higher than the softening point in the firing process described later, the encapsulation of gases generated from the organic component into the softened and flowing glass is suppressed, promoting the release of gas into the atmosphere, further suppressing the disconnection of conductive wiring at stepped sections caused by gas encapsulation into the glass, and further improving adhesion to the substrate. It is more preferable that the softening point of the glass frit is 100°C or more higher than the decomposition temperature of the organic component.

[0035] Here, the softening point of glass frit can be determined by TG-DTA measurement using a differential thermal and thermogravimetric simultaneous thermal analyzer (e.g., DTG-60; manufactured by Shimadzu Corporation). Furthermore, the decomposition temperature of the organic component refers to the temperature at which degassing begins when the organic component is heated, and this can be determined by TG-DTA measurement using a differential thermal and thermogravimetric simultaneous thermal analyzer (e.g., DTG-60; manufactured by Shimadzu Corporation).

[0036] The glass frit content in the photosensitive paste is preferably 10 to 25 volume percent of the total inorganic particles. Including 10 volume percent or more of glass frit increases the strength of the conductive wiring, further improves abrasion resistance and acid resistance, and enhances adhesion to the substrate. A glass frit content of 15 volume percent or more is more preferable. On the other hand, including 25 volume percent or less of glass frit allows the content of conductive particles in the inorganic particles to be easily set within the aforementioned preferred range. A glass frit content of 22 volume percent or less is more preferable.

[0037] It is preferable to further include silicon dioxide particles as inorganic particles. By including silicon dioxide particles, over-sintering can be suppressed in the firing process described later, the dispersibility of conductive particles and glass frit in the conductive wiring can be improved, and the acid resistance of the conductive wiring can be improved.

[0038] The silicon dioxide particle content in the photosensitive paste is preferably 5% by volume or more of the total inorganic particles. Including 5% by volume or more of silicon dioxide particles can further improve the acid resistance of the conductive wiring. On the other hand, the silicon dioxide particle content is preferably 10% by volume or less of the total inorganic particles. Including 10% by volume or less of silicon dioxide particles can suppress the inhibition of sintering of conductive particles during the firing process, improve conductivity, and further suppress the breakage of conductive wiring at stepped sections.

[0039] It is preferable that the organic components include an alkali-soluble resin and a photosensitive component. A photosensitive paste containing such organic components can be patterned by photolithography.

[0040] Alkali-soluble resins are resins that have alkali-soluble groups. Examples of alkali-soluble groups include carboxyl groups, phenolic hydroxyl groups, sulfonic acid groups, and thiol groups. A resin may have two or more of these groups. Among these, carboxyl groups are preferred due to their high solubility in alkaline developers.

[0041] As the alkali-soluble resin, acrylic resin is preferred, and copolymers of acrylic monomers having carbon-carbon double bonds and other monomers are preferred. Examples of acrylic monomers having carbon-carbon double bonds and other monomers include those exemplified as raw materials for acrylic resin, which is an example of alkali-soluble resin (b-1), in Japanese Patent Application Publication No. 2019-215446.

[0042] Acrylic resins preferably have carbon-carbon double bonds in their side chains or molecular ends, which can improve the curing reaction rate during exposure. Examples of structures having carbon-carbon double bonds include vinyl groups, allyl groups, acrylic groups, and methacrylic groups. Two or more of these may be present. Methods for introducing carbon-carbon double bonds into acrylic resins include, for example, reacting mercapto groups, amino groups, hydroxyl groups, and carboxyl groups in the acrylic resin with compounds having glycidyl groups or isocyanate groups and carbon-carbon double bonds, acrylic acid chloride, methacrylic acid chloride, allyl chloride, etc.

[0043] Examples of compounds having a glycidyl group and a carbon-carbon double bond include glycidyl methacrylate, glycidyl acrylate, allyl glycidyl ether, glycidyl ethyl acrylate, crotonyl glycidyl ether, glycidyl crotonate, glycidyl isocrotonate, and "Cychromer" (registered trademark) M100, A200 (all manufactured by Daicel Chemical Industries, Ltd.). Examples of compounds having an isocyanate group and a carbon-carbon double bond include acryloyl isocyanate, methacryloyl isocyanate, acryloylethyl isocyanate, and methacryloylethyl isocyanate. Two or more of these may be used.

[0044] Examples of photosensitive components include compounds having unsaturated double bonds, such as photopolymerization initiators and dissolution inhibitors. From the viewpoint of forming thicker wiring patterns, photopolymerization initiators and compounds having unsaturated double bonds are preferred.

[0045] Photopolymerization initiators impart photocurability to photosensitive pastes by absorbing and decomposing short-wavelength light such as ultraviolet light, or by generating radicals through a hydrogen abstraction reaction, thereby enabling pattern formation by negative-type photolithography. Examples of photopolymerization initiators include those exemplified as photoreaction initiator (d) in Japanese Patent Application Publication No. 2019-215446. From the viewpoint of photocurability, oxime-based photopolymerization initiators are preferred.

[0046] The dissolution inhibitor increases the solubility of the exposed areas of the photosensitive paste in the developer, enabling pattern formation by positive-type photolithography. Preferably, the dissolution inhibitor is one that generates acid due to the exposure energy used in the exposure process described later. For example, one is exemplified as a dissolution inhibitor among the photosensitive agents (d) in International Publication No. 2024 / 004461.

[0047] Examples of compounds having an unsaturated double bond include those exemplified as reactive monomers (D) having an unsaturated double bond in International Publication No. 2019 / 073926.

[0048] The thickness of the wiring pattern can be designed according to the desired thickness of the conductive wiring, with 3 to 30 μm being preferred. Furthermore, since the wiring pattern gradually deforms as it sintersects along the steps during the firing process, setting the thickness of the wiring pattern to 3 μm or more can further suppress wire breakage during firing. On the other hand, setting the thickness of the wiring pattern to 30 μm or less promotes the release of gases generated from organic components during firing into the atmosphere, further suppressing wire breakage at the steps.

[0049] Here, the thickness of the wiring pattern can be measured using a laser microscope (for example, VK-X3000; manufactured by Keyence Corporation). More specifically, it can be determined by magnifying the surface of the wiring pattern using a laser microscope, measuring the thickness at three randomly selected locations, and calculating the average value. The average value should be rounded to the nearest integer.

[0050] The adhesive layer is preferably formed by applying an adhesive, and examples of adhesives include acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, epoxy adhesives, polyvinyl alcohol adhesives, polyvinyl butyral adhesives, and polyolefin adhesives. Two or more of these may be used.

[0051] The adhesive layer may contain a filler. From the viewpoint of improving conductivity, the filler content in the adhesive layer is preferably 10% by mass or less.

[0052] As mentioned above, the adhesive layer may be patterned by photolithography of a photosensitive adhesive layer. In this case, it is preferable that the photosensitive adhesive layer further contains a photosensitive component. Examples of photosensitive components include those exemplified as photosensitive components of photosensitive paste. Furthermore, the following embodiments of the adhesive layer are also common when it is patterned.

[0053] The thickness of the adhesive layer is preferably 1 to 50 μm. By making the thickness of the adhesive layer 1 μm or more, the handling of the adhesive layer / wiring pattern-attached release substrate laminate, the adhesive layer pattern / wiring pattern-attached release substrate laminate, and the adhesive layer / substrate laminate can be improved, and disconnection caused by the wiring pattern directly contacting the substrate can be further suppressed. In addition, it is easily deformed in the out-of-plane direction during the transfer process and functions as a buffer material that absorbs steps. The thickness of the adhesive layer is more preferably 3 μm or more. On the other hand, by making the thickness of the adhesive layer 50 μm or less, disconnection of conductive wiring at steps caused by the inclusion of gas generated from the adhesive can be further suppressed during the firing process described later, and the adhesion between the conductive wiring and the substrate can be further improved. In the firing process described later, if there is no step of heat treatment at a temperature lower than the softening point of the glass frit for 5 minutes or more, the thickness of the adhesive layer is more preferably 10 μm or less, and even more preferably 7 μm or less. On the other hand, in the firing process described later, if the glass frit is heat-treated at a temperature lower than its softening point for 5 minutes or more, and then fired at a temperature higher than its softening point, even with a thick adhesive layer, the disconnection of conductive wiring at stepped portions caused by gas encapsulation in the glass can be further suppressed, and the adhesion between the conductive wiring and the substrate can be improved. Therefore, a thickness of 10 μm or more is more preferable for the adhesive layer.

[0054] Here, the thickness of the adhesive layer can be measured using a laser microscope (e.g., VK-X3000; manufactured by Keyence Corporation). More specifically, the thickness can be determined by magnifying the surface of the adhesive layer with a laser microscope, measuring the thickness at three randomly selected locations, and calculating the average value. However, when measuring from an adhesive layer / release substrate laminate with wiring patterns, the thickness of the adhesive layer refers to the height from the release substrate and is measured in the area without wiring patterns. The average value should be rounded to the nearest integer.

[0055] A photosensitive paste can be obtained, for example, by dissolving and / or dispersing the aforementioned alkali-soluble resin, photosensitive component, and other components as needed in a solvent. Examples of apparatus for dissolving and / or dispersing include dispersers such as three-roller mixers and ball mills, as well as kneaders. Dissolving and / or dispersing may be carried out at room temperature or under heating.

[0056] The process of forming a wiring pattern on a release substrate by photolithography using a photosensitive paste preferably includes the steps of applying the photosensitive paste to the release substrate to form a photosensitive layer, exposing it to light, and developing it.

[0057] Methods for applying the photosensitive paste to a release substrate include, for example, spray coating, roll coating, screen printing, and coating methods using coaters such as blade coaters, die coaters, calender coaters, meniscus coaters, and bar coaters. Among these, screen printing is preferred from the viewpoint of suitability for thick film coating and continuous productivity. The coating film thickness can be appropriately selected depending on the coating method, the solid content concentration and viscosity of the photosensitive paste, etc.

[0058] After applying the photosensitive paste, it may be dried as needed. Drying methods include, for example, heat drying using a heating device such as an oven, hot plate, or infrared, or vacuum drying. A heating temperature of 60-120°C is preferred. A heating time of 5 minutes to several hours is preferred.

[0059] Exposure methods include, for example, a method of fully exposing the photosensitive layer, a method of partially exposing the photosensitive layer through a photomask, and a method of partially exposing the photosensitive layer using laser light or the like. Exposure apparatuses include, for example, stepper exposure machines and proximity exposure machines. Active light rays for exposure include, for example, near-ultraviolet light, ultraviolet light, electron beams, X-rays, and laser light, with ultraviolet light being preferred. Light sources for ultraviolet light include, for example, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, halogen lamps, and germicidal lamps, with ultra-high-pressure mercury lamps being preferred.

[0060] Examples of development methods include spraying a developer onto the photosensitive layer of a release substrate with a photosensitive layer formed on it while the substrate is stationary or rotating; immersing the release substrate with the photosensitive layer formed on it in a developer; and applying ultrasonic waves while immersing the release substrate with the photosensitive layer formed on it in a developer.

[0061] As the developer, an alkaline developer is preferred, and examples include inorganic alkaline developers and organic alkaline developers. Examples of inorganic alkaline developers include sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate. Examples of organic alkaline developers include those exemplified as developers for alkaline development in Japanese Patent Publication No. 2019-215446.

[0062] Among these, inorganic alkaline developers are preferred. By developing with an inorganic alkaline developer, alkali metal components are incorporated into the wiring pattern, which promotes the diffusion of conductive particles in the firing process described later, and allows sintering to proceed efficiently. In addition, the effect of alkali metal components moving into the substrate can further improve the adhesion between the conductive wiring and the substrate.

[0063] After development, the pattern may be rinsed with a rinsing solution. Examples of rinsing solutions include water; aqueous solutions of alcohols such as ethanol and isopropyl alcohol; and aqueous solutions of esters such as ethyl lactate and propylene glycol monomethyl ether acetate.

[0064] Methods for forming the adhesive layer include, for example, attaching an adhesive sheet with an adhesive layer formed on a support to the wiring pattern layer side of the release substrate with a wiring pattern in the case of an adhesive layer / release substrate laminate, or to the substrate in the case of an adhesive layer / substrate laminate, and then peeling off the support from the adhesive sheet. Methods for attaching the adhesive sheet include, for example, using a hand roller, a press machine, or a roll laminator.

[0065] The process of forming an adhesive layer pattern on a wiring pattern by photolithography using a photosensitive adhesive paste preferably includes the steps of applying a photosensitive adhesive paste onto a photosensitive layer to form a photosensitive adhesive layer, exposing the photosensitive layer and the photosensitive adhesive layer together to light, and developing. Examples of the application method, exposure method, and development method for the photosensitive adhesive paste include those exemplified as the application method, exposure method, and development method in the wiring pattern formation process, respectively.

[0066] In the transfer process, a release substrate with a wiring pattern having a wiring pattern on a release substrate and a substrate are placed with the wiring pattern facing the substrate side via an adhesive layer, and the wiring pattern is transferred to the substrate via the adhesive layer. When transferring the adhesive layer and wiring pattern to the substrate by placing an adhesive layer / release substrate laminate with a wiring pattern and a substrate with the adhesive layer facing the substrate side, when transferring the adhesive layer and wiring pattern to the substrate, when placing a release substrate with a wiring pattern and an adhesive layer / substrate laminate with the wiring pattern facing the adhesive layer side of the adhesive layer / substrate laminate, and transferring the wiring pattern to the adhesive layer / substrate laminate, or when placing an adhesive layer pattern / release substrate laminate with a wiring pattern and adhesive layer pattern having a laminate of wiring pattern and adhesive layer pattern on a release substrate and a substrate with the adhesive layer pattern facing the substrate side, methods for transferring the wiring pattern and, if necessary, the adhesive layer and adhesive layer pattern to the substrate or adhesive layer / substrate laminate include, for example, using a hand roller, a press machine, a roll laminator, etc.

[0067] (Peeling process) In the peeling process, the release substrate with the wiring pattern is peeled off. Possible peeling methods include folding the edge of the release substrate back 180° and pulling it parallel to the substrate to peel it off.

[0068] (Firing process) In the firing process, the wiring pattern and adhesive layer are fired to form conductive wiring on the substrate. As a result, the wiring pattern becomes conductive wiring, the adhesive layer component is removed by deash, and conductive wiring is directly formed on the substrate. As described above, in the technology described in Patent Document 1, the electrodeposited metal pattern is adhered to the substrate by an inorganic component that is heat-fused, whereas in the present invention, conductive wiring is formed directly on the substrate by deash removal of the adhesive layer component. Therefore, even when a substrate with steps on its surface is used, conductive wiring can be formed to follow the steps, and disconnection of the conductive wiring at the steps can be suppressed.

[0069] Examples of the firing method in the present invention include a method of performing heat treatment at 300 to 1,500°C for 5 minutes to several hours. Alternatively, a method may be used in which heat treatment is performed at 300 to 700°C for 5 minutes to several hours, followed by further heat treatment at 700°C or higher for 5 minutes to several hours. When the wiring pattern contains glass frit, firing is preferably performed at a temperature higher than the softening point of the glass frit. By firing at a temperature higher than the softening point of the glass frit, entrapment of gas generated from organic components in the softening and flowing glass is suppressed, gas release to the atmosphere is promoted, disconnection of the conductive wiring at the stepped portion caused by gas entrapment in the glass is further suppressed, and the adhesion between the conductive wiring and the base material can be improved. It is also preferable to perform heat treatment at a temperature lower than the softening point of the glass frit for 5 minutes or more, and then perform firing at a temperature higher than the softening point of the glass frit. By performing the heat treatment at a temperature lower than the softening point of the glass frit for 5 minutes or more, the adhesive layer component can be sufficiently removed by decalcification. In particular, when the thickness of the adhesive layer is 10 μm or more, gas generated from the adhesive tends to be easily entrapped, and the adhesion between the conductive wiring and the base material tends to be difficult to maintain. However, by using such a method, even for a thick-film adhesive layer, disconnection of the conductive wiring at the stepped portion caused by gas entrapment in the glass can be further suppressed, and the adhesion between the conductive wiring and the base material can be improved. In addition, when the adhesive layer is patterned, decalcification and removal of the adhesive layer component in the firing step can proceed efficiently, so that even for a thick-film adhesive layer, disconnection of the conductive wiring at the stepped portion caused by gas entrapment in the glass can be further suppressed, and the adhesion between the conductive wiring and the base material can be improved.

[0070] In the present invention, when the height of the step is defined as T0 μm, and the thickness of the wiring pattern is defined as T a μm, and the thickness of the adhesive layer is defined as T b μm, it is preferable that T0, T a and T b satisfy the following formula (1). T a ×T b ≧T0(1) The adhesive layer is easily deformed in the out-of-plane direction during the transfer step, and its thickness T bThe larger the thickness T, the more effectively it functions as a cushioning material to absorb the step. On the other hand, the wiring pattern gradually deforms as it sinters along the step during the firing process, so its thickness T a The larger the value, the more sufficient deformation can be secured. Step-following ability is due to the synergistic effect of the contributions of both, so the product of these (T a ×T b This allows us to represent the combined effect of the cushioning effect of the adhesive layer and the deformation of the wiring pattern. In other words, by satisfying the relationship in equation (1) above, even when the height of the step is large, stress concentration at the step can be reduced and the breakage of conductive wiring can be further suppressed.

[0071] The manufacturing method of the present invention also allows for the formation of conductive wiring across both sides and the sides of the substrate.

[0072] Next, the method for manufacturing the laminate of the present invention will be described. In the present invention, the laminate has conductive wiring and a green sheet on a green sheet. The method for manufacturing the laminate of the present invention comprises, in this order, a transfer step in which a release substrate with a wiring pattern having a wiring pattern on a release substrate and a first green sheet are placed with an adhesive layer in between so that the wiring pattern faces the first green sheet, and the wiring pattern is transferred to the first green sheet via the adhesive layer; a peeling step in which the release substrate is peeled off; a lamination step in which a second green sheet is laminated on the wiring pattern side; and a firing step in which the wiring pattern and adhesive layer are fired to form conductive wiring between the green sheets.

[0073] Examples of green sheets include those having an insulating composition layer containing inorganic powder, binder resin, and optionally other components on a substrate such as a plastic film or an optical resin plate. A green sheet can be obtained, for example, by applying the aforementioned insulating composition to the aforementioned substrate and drying it as necessary to form an insulating composition layer. Examples of application methods include the method exemplified as the application method for the photosensitive paste described above.

[0074] As a method for manufacturing the laminate of the present invention, in addition to the method for manufacturing the conductive wiring substrate of the present invention described above, a method is provided in which a first green sheet is used as the base material in the transfer step, and a lamination step is provided between the peeling step and the firing step in which a second green sheet is laminated on the wiring pattern side.

[0075] Next, the method for manufacturing the multilayer laminate of the present invention will be described. In the present invention, a multilayer laminate is made by laminating conductive wiring and multiple green sheets on a green sheet. The method for manufacturing the multilayer laminate of the present invention is to produce multiple green sheets with adhesive layers by arranging a release substrate with a wiring pattern having a wiring pattern on a release substrate and a first green sheet with an adhesive layer in such a way that the wiring pattern faces the first green sheet side via an adhesive layer, and then having a transfer step in which the wiring pattern is transferred to the first green sheet via the adhesive layer and a peeling step in which the release substrate is peeled off, thereby producing multiple green sheets with adhesive layers having an adhesive layer, laminating the obtained multiple green sheets with adhesive layers having an adhesive layer, and then having a lamination step in which a second green sheet is placed on the wiring pattern side of the outermost surface and the two are laminated together, and then having a firing step in which the wiring pattern and adhesive layer are fired to form conductive wiring between the green sheets.

[0076] As a method for manufacturing a multilayer laminate of the present invention, in addition to the method for manufacturing a laminate of the present invention described above, a method is provided in which a plurality of green sheets with wiring patterns having an adhesive layer are manufactured by replacing the transfer step and the peeling step with a method having the transfer step and the peeling step in that order, the plurality of green sheets with wiring patterns having adhesive layers obtained are laminated, and a second green sheet is placed on the wiring pattern side of the outermost surface, and the laminates are laminated all at once. [Examples]

[0077] The present invention will be described in more detail below with reference to examples and comparative examples. First, the materials used in each example and comparative example will be explained.

[0078] [Conductive particles] Silver particles: median diameter (D50) 2.1 μm, resistivity 1.6 × 10⁻¹⁰ at 20°C -8 Ω·cm silver particles The median diameter (D50) of the silver particles was measured using a particle size distribution analyzer (Microtrac HRA Model No. 9320-X100; manufactured by Nikkiso Co., Ltd.) by laser light scattering.

[0079] [Glass frit] • Glass frit (a-1): GF3580 (manufactured by Okuno Pharmaceutical Co., Ltd.) Softening point 578°C (Main composition system: Bi2O3-SiO2-B2O3) • Glass frit (a-2): GF4550 (manufactured by Okuno Pharmaceutical Co., Ltd.) Softening point 575°C (Main composition system: ZnO-SiO2-B2O3-R2O) • Glass frit (a-3): GF3500 (manufactured by Okuno Pharmaceutical Co., Ltd.) Softening point 495°C (Main composition system: Bi2O3-SiO2-B2O3) • Glass frit (a-4): GF3410 (manufactured by Okuno Pharmaceutical Co., Ltd.) Softening point 414℃ (Main composition system: Bi2O3-ZnO-B2O3) • Glass frit (a-5): GF5780 (manufactured by Okuno Pharmaceutical Co., Ltd.) Softening point 780℃ (Main composition system: SiO2-B2O3-RO) Here, R2O is a general term for Li2O, Na2O, and K2O, and RO is a general term for MgO, CaO, BaO, and SrO. The softening point of the glass frit was determined by TG-DTA measurement using a differential thermal and thermogravimetric simultaneous thermal analyzer DTG-60 (manufactured by Shimadzu Corporation).

[0080] [Silicon dioxide particles] Aerosil R972: Median diameter (D50) 12nm, insulating silica powder "AEROSIL®" R972 (manufactured by Nippon Aerosil Co., Ltd.) Here, the median diameter (D50) of Aerosil R972 was measured using a dynamic light scattering particle size distribution analyzer "NANOTRAC®" WAVEII-UZ251 (manufactured by MicrotracBEL) after adding Aerosil R972 to water and performing sonication for 300 seconds.

[0081] [Release base material] Release substrate consisting of a PET film (thickness 125 μm) coated with AL-5 (Lintec Corporation, long-chain alkyl release agent, release force 1480 mN / 20 mm) [Adhesive sheet] An acrylic adhesive, "SK Dyne®" 1502C (manufactured by Soken Chemical Co., Ltd.), was applied to a PET film and dried to form an adhesive layer. The thickness of the adhesive layer was as follows: • Adhesive sheet b-0: Adhesive layer thickness 3μm • Adhesive sheet b-1: Adhesive layer thickness 5μm • Adhesive sheet b-2: Adhesive layer thickness 8μm • Adhesive sheet b-3: Adhesive layer thickness 12μm • Adhesive sheet b-4: Adhesive layer thickness 20μm • Adhesive sheet b-5: Adhesive layer thickness 40μm • Adhesive sheet b-6: Adhesive layer thickness 60μm Furthermore, a glass frit-containing adhesive, prepared by mixing the acrylic adhesive "SK Dyne®" 1502C (manufactured by Soken Chemical Co., Ltd.) and glass frit (a-1) in a mass ratio of 7:3, was applied to a PET film and dried to form an adhesive layer with a thickness of 5 μm, which was then used to create adhesive sheet b-7.

[0082] [Base material] • Stepped glass substrate: A glass substrate having a decorative area made of black ceramic resin on a portion of its surface, with step heights of 12 μm, 15 μm, 20 μm, 30 μm, 40 μm, and 60 μm between the decorative and undecorated areas. The step height was determined by using a stylus-type step meter "Surfcom (registered trademark)" 1400 (manufactured by Tokyo Seimitsu Co., Ltd.) to measure the height from the substrate at three randomly selected locations on the stepped area, under the conditions of measuring length: 1 mm and scanning speed: 0.3 mm / second. The average value of these measurements was calculated and rounded to the nearest tenth.

[0083] [Synthesis Example 1: Alkali-Soluble Resin] 150 g of dimethylaminomethanol (hereinafter, "DMEA"; manufactured by Tokyo Chemical Industry Co., Ltd.) was charged into a reaction vessel under a nitrogen atmosphere, and the temperature was raised to 80°C using an oil bath. A mixture consisting of 20 g of ethyl acrylate (hereinafter, "EA"), 40 g of 2-ethylhexyl methacrylate (hereinafter, "2-EHMA"), 20 g of styrene (hereinafter, "St"), 15 g of acrylic acid (hereinafter, "AA"), 0.8 g of 2,2'-azobisisobutyronitrile and 10 g of DMEA was added dropwise over 1 hour. After the addition was complete, the polymerization reaction was carried out by heating at 80°C under a nitrogen atmosphere for 6 hours. Subsequently, 1 g of hydroquinone monomethyl ether was added to stop the polymerization reaction. Subsequently, a mixture consisting of 5 g of glycidyl methacrylate (hereinafter, "GMA"), 1 g of triethylbenzylammonium chloride and 10 g of DMEA was added dropwise over 0.5 hours. After the dropwise addition was complete, the mixture was heated at 80°C under a nitrogen atmosphere for 2 hours to carry out the addition reaction. The resulting reaction solution was purified with methanol to remove unreacted impurities, and then vacuum-dried for 24 hours to obtain an alkali-soluble resin with a copolymerization ratio (by mass): EA / 2-EHMA / St / GMA / AA = 20 / 40 / 20 / 5 / 15. The acid value of the obtained alkali-soluble resin was 103 mg KOH / g.

[0084] [Preparation Example 1: Photosensitive Paste 1] In a 100 mL clean bottle, 10.0 g of the alkali-soluble resin obtained in Synthesis Example 1, 0.50 g of "ADEKA ARCULUS®" N-1919T (oxime-based photopolymerization initiator; manufactured by ADEKA Corporation) as a photopolymerization initiator, 5.0 g of DMEA as a solvent, and 2.0 g of "Light Acrylate®" BP-4EA (manufactured by Kyoeisha Chemical Co., Ltd.) as a compound having an unsaturated double bond were placed and mixed using a rotation-revolution vacuum mixer "Awatori Rentaro®" ARE-310 (manufactured by Thinky Co., Ltd.) to obtain 17.50 g of organic component solution (solid content 71.4% by mass).

[0085] The obtained 17.50 g of organic component solution, 33.42 g of silver particles, 4.80 g of glass frit (a-1), and 0.80 g of Aerosil R972 were mixed and kneaded using a three-roller mill "EXAKT®" M-50 (manufactured by EXAKT Corporation) to obtain 56.52 g of photosensitive paste 1.

[0086] [Preparation Example 2: Photosensitive Paste 2] A photosensitive paste 2 was prepared in the same manner as in Preparation Example 1, except that 18.38 g of silver particles, 2.64 g of glass frit (a-1), and 0.44 g of Aerosil R972 were used. 38.96 g of this paste was obtained.

[0087] [Preparation Example 3: Photosensitive Paste 3] A photosensitive paste 3 was prepared in the same manner as in Preparation Example 1, except that 46.79 g of silver particles, 6.71 g of glass frit (a-1), and 1.13 g of Aerosil R972 were used. 72.14 g of this paste was obtained.

[0088] [Preparation Example 4: Photosensitive Paste 4] A photosensitive paste 4 was prepared in the same manner as in Preparation Example 1, except that 38.22 g of silver particles, 3.57 g of glass frit (a-1), and 0.85 g of Aerosil R972 were used. 60.14 g of this paste was obtained.

[0089] [Preparation Example 5: Photosensitive Paste 5] A photosensitive paste 5 was prepared in the same manner as in Preparation Example 1, except that 31.99 g of silver particles, 5.83 g of glass frit (a-1), and 0.82 g of Aerosil R972 were used.

[0090] [Preparation Example 6: Photosensitive Paste 6] A photosensitive paste 6 was prepared in the same manner as in Preparation Example 1, except that 38.81 g of silver particles, 1.98 g of glass frit (a-1), and 0.80 g of Aerosil R972 were used.

[0091] [Preparation Example 7: Photosensitive Paste 7] A photosensitive paste 7 was prepared in the same manner as in Preparation Example 1, except that 33.11 g of silver particles, 7.55 g of glass frit (a-1), and 0.91 g of Aerosil R972 were used. A total of 59.07 g of photosensitive paste 7 was obtained.

[0092] [Preparation Example 8: Photosensitive Paste 8] A photosensitive paste 8 was prepared in the same manner as in Preparation Example 1, except that 32.92 g of silver particles, 2.72 g of glass frit (a-2), and 0.79 g of Aerosil R972 were used. A total of 53.93 g of this paste was obtained.

[0093] [Preparation Example 9: Photosensitive Paste 9] A photosensitive paste 9 was prepared in the same manner as in Preparation Example 1, except that 34.90 g of silver particles, 5.85 g of glass frit (a-3), and 0.84 g of Aerosil R972 were used.

[0094] [Preparation Example 10: Photosensitive Paste 10] A photosensitive paste 10 was prepared in the same manner as in Preparation Example 1, except that 34.23 g of silver particles, 6.53 g of glass frit (a-4), and 0.83 g of Aerosil R972 were used.

[0095] [Preparation Example 11: Photosensitive Paste 11] A photosensitive paste 11 was prepared in the same manner as in Preparation Example 1, except that 35.03 g of silver particles, 2.80 g of glass frit (a-5), and 0.85 g of Aerosil R972 were used.

[0096] [Preparation Example 12: Photosensitive Paste 12] A photosensitive paste 12 was prepared in the same manner as in Preparation Example 1, except that 34.16 g of silver particles, 4.57 g of glass frit (a-1), and 0.29 g of Aerosil R972 were used.

[0097] [Preparation Example 13: Photosensitive Paste 13] A photosensitive paste 13 was prepared in the same manner as in Preparation Example 1, except that 32.92 g of silver particles, 4.95 g of glass frit (a-1), and 1.17 g of Aerosil R972 were used.

[0098] [Preparation Example 14: Photosensitive Paste 14] A photosensitive paste 14 was prepared in the same manner as in Preparation Example 1, except that 8.75 g of the organic component solution obtained in the same manner as in Preparation Example 1, 55.15 g of silver particles, 7.91 g of glass frit (a-1), and 1.33 g of Aerosil R972 were used.

[0099] [Preparation Example 15: Photosensitive Adhesive Paste] In a 100 mL clean bottle, 13.59 g of the alkali-soluble resin obtained in Synthesis Example 1, 2.04 g of "JONCRYL®" 819 (alkali-soluble resin; manufactured by BASF Japan Ltd.), 0.60 g of OXE04 (oxime-based photopolymerization initiator; manufactured by BASF Japan Ltd.), 2.00 g of "Light Acrylate®" BP-4EA (manufactured by Kyoeisha Chemical Co., Ltd.) as a compound having an unsaturated double bond, and 5.23 g of DGME as a solvent were added and mixed using a rotation-revolution vacuum mixer "Awatori Rentaro®" ARE-310 (manufactured by Thinky Co., Ltd.) to obtain 23.46 g of photosensitive adhesive paste.

[0100] [Developer] • Developer 1: 0.1% by mass sodium carbonate aqueous solution • Developer 2: 0.5% by mass aqueous solution of tetramethylammonium hydroxide [Firing conditions] • Baking conditions 1: Bake at 700°C for 10 minutes. • Baking conditions 2: Bake at 900°C for 10 minutes. • Firing condition 3: Firing at 420°C for 30 minutes, then firing at 700°C for 10 minutes.

[0101] Next, the evaluation methods for each example and comparative example will be described.

[0102] [Broken wire at the step] For each example and comparative example, 100 conductive wiring boards for wire breakage evaluation were manufactured, and their resistance was measured using a digital multimeter (CDM-16D; manufactured by Custom Co., Ltd.). A wire breakage was determined if the resistance could not be measured. The percentage of wire breakage boards out of 100 was defined as the wire breakage probability.

[0103] [Conductive] For each example and comparative example, the conductive wiring substrates manufactured for conductivity evaluation were examined using a scanning electron microscope (S2400; Hitachi, Ltd.) at a magnification of 2,000x. The line width was measured at three randomly selected locations on the wiring pattern, and the average value was calculated. Additionally, the surface of the wiring pattern was examined using a laser microscope (VK-X3000; Keyence Corporation), and the thickness was measured at three randomly selected locations, and the average value was calculated. Furthermore, the resistance between pads of the conductive wiring was measured using a digital multimeter (CDM-16D; Custom Corporation), and the resistivity was calculated using the following formula. The values ​​were rounded to one decimal place by rounding to two decimal places. Resistivity (μΩ·cm) = Resistance (Ω) × 1,000 × Wire width of conductive wire (cm) × Thickness of conductive wire (cm) ÷ Length of conductive wire (cm) The lower the resistivity, the better the conductivity.

[0104] [Adhesion] For each example and comparative example, cellophane tape as specified in JIS Z 1522 was applied to the 5cm square solid area and the pattern areas with line widths of 50μm, 30μm, and 15μm of the conductive wiring boards manufactured for adhesion evaluation. After peeling off the tape, the boards were observed under magnification of 1,000x using an optical microscope. A "○" was indicated if neither disconnection nor peeling was observed, and a "×" was indicated if disconnection and / or peeling was observed.

[0105] [Acid resistance] The solid areas and pattern areas with line widths of 50 μm, 30 μm, and 15 μm of the conductive wiring boards used for adhesion evaluation, which were evaluated as "○" in the adhesion evaluation described above, were immersed in a 0.1 N sulfuric acid aqueous solution (liquid temperature 23°C) for 2 hours. Then, cellophane tape was applied and peeled off in the same manner as in the adhesion evaluation method, and the areas were observed under magnification of 1,000x using an optical microscope. If neither disconnection nor peeling was observed, it was marked as "○", and if disconnection and / or peeling was observed, it was marked as "×".

[0106] [Abrasion resistance] The pencil hardness of a 5cm square solid area of ​​the conductive wiring board for adhesion evaluation manufactured in each example and comparative example was measured in accordance with JIS K 5600-5-4 (1999).

[0107] (Example 1) The photosensitive paste 1 obtained in Preparation Example 1 was applied to the release substrate by screen printing so that the film thickness after drying was 10 μm, and a coated film was obtained. The obtained coated film was dried in a hot air dryer at 80°C for 10 minutes to form a photosensitive layer on the release substrate. An exposure mask with an opening of 5 cm in length and 1 mm in line width, and 1 cm square pads at both ends, was used at 21 mW / cm². 2 Ultra-high pressure mercury lamp with output of 500 mJ / cm² 2 Exposure (calculated at a wavelength of 365 nm) was performed. Subsequently, a 0.1 mass% sodium carbonate aqueous solution was used as a developer, and shower development was performed until all unexposed areas were dissolved, forming a wiring pattern on the release substrate. Adhesive sheet b-1 was laminated over the entire surface, including the wiring pattern, using a roll laminator at a temperature of 30°C to obtain an adhesive layer / release substrate laminate with wiring pattern. The obtained adhesive layer / release substrate laminate and the substrate were bonded together with the adhesive layer facing the substrate, and the adhesive layer and wiring pattern were transferred so that the wiring pattern crossed the steps of the substrate. After that, the release substrate was peeled off, and the substrate was fired at 700°C for 10 minutes to produce a conductive wiring substrate for conductivity evaluation.

[0108] Conductive wiring boards for evaluating wire breakage and conductive wiring boards for evaluating adhesion were fabricated in the same manner as described above, except that an exposure mask with a length of 5 cm and a line width of 1 mm and openings with 1 cm square pads at both ends, and an exposure mask with a 5 cm square solid area and openings with pattern areas with line widths of 50 μm, 30 μm, and 15 μm were used as exposure masks.

[0109] (Examples 2-11) A conductive wiring board was fabricated in the same manner as in Example 1, except that the photosensitive paste was changed as described in Table 1, and each evaluation was performed.

[0110] (Example 12) A conductive wiring board was fabricated in the same manner as in Example 11, except that the firing conditions were changed to 900°C for 10 minutes, and each evaluation was performed.

[0111] (Examples 13-14) A conductive wiring board was fabricated in the same manner as in Example 1, except that the photosensitive paste was changed as described in Table 2, and each evaluation was performed.

[0112] (Examples 15, 16) Conductive wiring boards were fabricated in the same manner as in Examples 1 and 5, except that the developer was changed to a 0.5% by mass aqueous solution of tetramethylammonium hydroxide, and each evaluation was performed.

[0113] (Examples 17, 18) A conductive wiring board was fabricated in the same manner as in Example 1, except that the adhesive sheet was changed as described in Table 2, and each evaluation was performed.

[0114] (Comparative Example 1) When the wiring pattern was transferred to a glass substrate without using an adhesive sheet, the wiring pattern could not be transferred.

[0115] (Comparative Example 2) A conductive wiring substrate was fabricated in the same manner as in Example 1, except that the adhesive sheet was changed as described in Table 2, and each evaluation was performed. A heat-sealed deposit of glass frit derived from the adhesive sheet was present between the substrate and the conductive wiring.

[0116] (Comparative Example 3) Conductive wiring boards were fabricated in the same manner as in Example 1, except that the photosensitive paste was changed as described in Table 2, and each evaluation was performed.

[0117] (Examples 19-21) A conductive wiring board was fabricated in the same manner as in Example 1, except that the adhesive sheet was changed as described in Table 3, and the firing conditions were changed to firing at 420°C for 30 minutes followed by firing at 700°C for 10 minutes. Each evaluation was then performed.

[0118] (Examples 22-31) A conductive wiring substrate was fabricated in the same manner as in Example 1, except that the thickness of the wiring pattern film, the thickness of the adhesive layer, the height of the step in the substrate, and the firing conditions were changed as described in Table 4, and each evaluation was performed.

[0119] (Example 32) A photosensitive paste 9 obtained in Preparation Example 9 was applied to a release substrate by screen printing so that the film thickness after drying was 10 μm, and a coated film was obtained. The obtained coated film was dried in a hot air dryer at 80°C for 10 minutes to form a photosensitive layer on the release substrate. Subsequently, a photosensitive adhesive paste obtained in Preparation Example 15 was applied by screen printing so that the film thickness after drying was 5 μm, and a coated film was obtained. The obtained coated film was dried in a hot air dryer at 80°C for 10 minutes to form a laminate of the photosensitive layer and the photosensitive adhesive layer. An exposure mask with an opening of 5 cm in length and 1 mm in line width, and 1 cm square pads at both ends, was used at 21 mW / cm². 2 Ultra-high pressure mercury lamp with output of 500 mJ / cm² 2Exposure (calculated at a wavelength of 365 nm) was performed. Subsequently, a 0.1 mass% sodium carbonate aqueous solution was used as a developer, and shower development was performed until all unexposed areas were dissolved, forming a laminate of the adhesive layer pattern and the wiring pattern on the release substrate. The resulting adhesive layer pattern / wiring pattern-attached release substrate laminate and the substrate were bonded together with the adhesive layer pattern facing the substrate. The adhesive layer pattern and wiring pattern were transferred so that the wiring pattern crossed the steps of the substrate, then the release substrate was peeled off, and the substrate was fired at 700°C for 10 minutes to produce a conductive wiring substrate for conductivity evaluation.

[0120] Conductive wiring boards for evaluating wire breakage and conductive wiring boards for evaluating adhesion were fabricated in the same manner as described above, except that an exposure mask with a length of 5 cm and a line width of 1 mm and openings with 1 cm square pads at both ends, and an exposure mask with a 5 cm square solid area and openings with pattern areas with line widths of 50 μm, 30 μm, and 15 μm were used as exposure masks.

[0121] (Example 33) A conductive wiring board was fabricated in the same manner as in Example 32, except that the photosensitive paste was changed as described in Table 5, and each evaluation was performed.

[0122] (Example 34) Conductive wiring boards were fabricated in the same manner as in Example 32, except that the photosensitive paste was changed as described in Table 5 and the firing conditions were changed to 900°C for 10 minutes, and each evaluation was performed.

[0123] Tables 1-5 show the main compositions and evaluation results for each example and comparative example.

[0124] [Table 1]

[0125] [Table 2]

[0126] [Table 3]

[0127] [Table 4]

[0128] [Table 5] [Explanation of Symbols]

[0129] 1: Release base material 2: Wiring Pattern 3:Adhesive layer 4: Base material 5: Conductive wiring 6: Stepped section 7: Substrate with steps 8: Photosensitive adhesive layer 9: Adhesive layer pattern 10: Photosensitive layer

Claims

1. A method for manufacturing a conductive wiring substrate having conductive wiring on a substrate, A transfer process involves arranging a release substrate with a wiring pattern having a wiring pattern on the release substrate and a base material with an adhesive layer in between so that the wiring pattern faces the base material, and transferring the wiring pattern to the base material via the adhesive layer. A peeling process to remove the release substrate, and a firing process in which the wiring pattern and adhesive layer are fired to form conductive wiring on the substrate, It has them in this order, The wiring pattern contains inorganic particles and organic components, and the inorganic particle content in the wiring pattern is 60 to 90% by mass. A method for manufacturing conductive wiring boards.

2. In the aforementioned transfer process, A laminate of adhesive layer / release substrate with a wiring pattern having a wiring pattern and an adhesive layer on a release substrate, and a substrate are placed so that the adhesive layer faces the substrate, and the adhesive layer and wiring pattern are transferred to the substrate. A method for manufacturing a conductive wiring board according to claim 1.

3. In the aforementioned transfer process, A release substrate with a wiring pattern having a wiring pattern on the release substrate and an adhesive layer / substrate laminate having an adhesive layer on the substrate are arranged so that the wiring pattern faces the adhesive layer side of the adhesive layer / substrate laminate, and the wiring pattern is transferred to the adhesive layer / substrate laminate. A method for manufacturing a conductive wiring board according to claim 1.

4. In the aforementioned transfer process, A laminate of adhesive layer pattern / release substrate with an adhesive layer pattern, having a laminate of a wiring pattern and an adhesive layer pattern on a release substrate, and a substrate are arranged so that the adhesive layer pattern faces the substrate, and the adhesive layer pattern and wiring pattern are transferred to the substrate. A method for manufacturing a conductive wiring board according to claim 1.

5. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, wherein the conductive wiring contains silver, copper, palladium, molybdenum, tungsten and / or nickel.

6. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, wherein the substrate has a step on its surface.

7. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, comprising the step of forming a wiring pattern on the release substrate by photolithography using a photosensitive paste containing inorganic particles and organic components, wherein the organic components contain photosensitive components.

8. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, wherein the inorganic particles contain 10 to 25 volume percent of glass frit in the total inorganic particles.

9. The method for manufacturing a conductive wiring substrate according to claim 8, wherein the glass frit contains bismuth oxide.

10. The method for manufacturing a conductive wiring substrate according to claim 8, wherein the glass frit has a softening point in the range of 420 to 800°C, the softening point is higher than the decomposition temperature of the organic component with the highest decomposition temperature among the organic components in the wiring pattern and the adhesive layer, and in the firing step, the glass frit is fired at a temperature higher than the softening point.

11. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, wherein the inorganic particles contain silicon dioxide particles in an amount of 5 volume% or more of the total inorganic particles.

12. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, wherein the thickness of the adhesive layer is 1 to 50 μm.

13. A method for manufacturing a conductive wiring substrate according to claim 10, wherein in the firing step, the material is heat-treated at a temperature lower than the softening point of the glass frit for 5 minutes or more, and then fired at a temperature higher than the softening point of the glass frit.

14. The method for manufacturing a conductive wiring substrate according to claim 13, wherein the thickness of the adhesive layer is 10 to 50 μm.

15. The height of the step is T 0 μm, the thickness of the wiring pattern is T a μm, the thickness of the adhesive layer is T b When T is μm, 0 , T a and T b A method for manufacturing a conductive wiring substrate according to claim 6, wherein the following formula (1) is satisfied. T a ×T b ≧T 0 (1)

16. A method for manufacturing a conductive wiring substrate according to any one of claims 1 to 4, wherein the conductive wiring extends across both sides and sides of the substrate.

17. A method for manufacturing a laminate having conductive wiring and a green sheet on a green sheet, A transfer process in which a release substrate with a wiring pattern having a wiring pattern on it and a first green sheet are placed with an adhesive layer in between so that the wiring pattern faces the first green sheet, and the wiring pattern is transferred to the first green sheet via the adhesive layer. A peeling process to remove the release substrate, The lamination process involves stacking the second green sheet on the wiring pattern side. and a firing process in which the wiring pattern and adhesive layer are fired to form conductive wiring between the green sheets, It has them in this order, The wiring pattern contains inorganic particles and organic components, and the inorganic particle content in the wiring pattern is 60 to 90% by mass. A method for manufacturing laminates.

18. A method for manufacturing a multilayer laminate comprising conductive wiring and multiple green sheets stacked on a green sheet, A method is used to manufacture multiple green sheets with adhesive layers and wiring patterns by arranging a release substrate with a wiring pattern having a wiring pattern on a release substrate and a first green sheet with an adhesive layer in such a way that the wiring pattern faces the first green sheet side via the adhesive layer, and then performing a transfer step to transfer the wiring pattern to the first green sheet via the adhesive layer and a peeling step to peel off the release substrate, and then stacking the obtained multiple green sheets with adhesive layers and wiring patterns, and further stacking a second green sheet on the outermost wiring pattern side and stacking them all at once. and a firing process in which the wiring pattern and adhesive layer are fired to form conductive wiring between the green sheets, It has them in this order, The wiring pattern contains inorganic particles and organic components, and the inorganic particle content in the wiring pattern is 60 to 90% by mass. A method for manufacturing a multilayer laminate.

Citation Information

Patent Citations

  • Heat-resistant wiring board

    JP1999251722A

  • Baking transfer film and forming method of base with functional pattern

    JP2008307729A

  • Method for producing ceramic green sheet with conductive pattern

    WO2024004461A1